Kajian Fitokimia Fraksi Etil Asetat dari Lichen Stereocaulon massartianum Hue. dan Uji Aktivitas Antibakteri dengan Metode KLT-Bioautografi - Friardi Ismed; Nadhifa Putri; Deddi Prima Putra (Jurnal Sains Farmasi & Klinis, 2020)
This research is a continuation study in the inventory of lichens of the genus Stereocaulon which is currently focused on the Stereocaulon massartianum Hue collected in the rocks of Diatas Lake, West Sumatera, Indonesia. Reports on phytochemical studies and pharmacological activities of this species are still limited, based on literature studies that have been carried out. This research was conducted to determine their secondary metabolites and potential antibacterial activity. The air-dried thallus of lichen S. massartianum was macerated successively using n-hexane, ethyl acetate and methanol solvents. The compounds were separated by chromatography and recrystallization methods, then analyzed by spectroscopy (UV-Vis, FTIR, 1H and 13C-NMR). Furthermore, the antibacterial activity assay was performed by agar diffusion method on ethyl acetate extract, and TLC-Bioautography for the isolated compound. Three compounds have been isolated from ethyl acetate extract, i.e. atranorin (1), stictic acid (2) and norstictic acid (3). The results of antibacterial assay from the extract showed antagonistic activity against pathogenic bacteria S. aureus, E. faecalis, E. coli, and P. aeruginosa at concentrations of 10 and 20%, while TLC-bioautography of compound 3 exhibited growth inhibition area in all test bacteria.